Cartilage scales embedded in fibrin gel - Kovacevic, Milos; Riedel, Frank; Bran, Gregor M. (Facial plastic surgery, 2017)
Multiple techniques have been described for dorsal nasal augmentation in rhinoplasty. In this article, we review common surgical techniques for raising the dorsum or eliminating dorsal irregularities, by highlighting inherent advantages and disadvantages of each method. Within the past few years, the use of diced cartilage grafts has become the workhorse in this field of interest. To overcome drawbacks of methods based on diced cartilage, we present a new concept for autologous augmentation, using regenerative medicine protocols. A mix of cartilage scales with cartilage pâté was embedded in platelet-rich fibrin (PRF). Since December 2015, a total of 48 patients were treated with this technique. Based on our preliminary results, cartilage scales in PRF appear to be a promising and reliable alternative to existing procedures for dorsal nasal augmentation.
Gesehen am 11.10.2018